2008
DOI: 10.1111/j.1365-2036.2008.03730.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical trial: asimadoline in the treatment of patients with irritable bowel syndrome

Abstract: SUMMARY BackgroundIn models of irritable bowel syndrome (IBS), asimadoline, a kappa-opioid agonist, improves pain and abnormal bowel function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
105
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(110 citation statements)
references
References 18 publications
(18 reference statements)
4
105
0
1
Order By: Relevance
“…In line with our animal studies, this indicates that immune cell-derived opioids do not produce cross-tolerance to exogenous opioid agonists, but may, in fact, prevent the development of tolerance at peripheral opioid receptors (Zöllner et al, 2008). Additional evidence for this notion has been provided using a peripherally acting -agonist in patients with irritable bowel disease, where a significant reduction in pain was observable over a treatment period of 3 months (Mangel et al, 2008). This implies that the use of peripherally acting opioid agonists for the prolonged treatment of inflammatory pain is not necessarily accompanied by tolerance.…”
Section: Novel Peripherally Restricted Opioidssupporting
confidence: 65%
See 3 more Smart Citations
“…In line with our animal studies, this indicates that immune cell-derived opioids do not produce cross-tolerance to exogenous opioid agonists, but may, in fact, prevent the development of tolerance at peripheral opioid receptors (Zöllner et al, 2008). Additional evidence for this notion has been provided using a peripherally acting -agonist in patients with irritable bowel disease, where a significant reduction in pain was observable over a treatment period of 3 months (Mangel et al, 2008). This implies that the use of peripherally acting opioid agonists for the prolonged treatment of inflammatory pain is not necessarily accompanied by tolerance.…”
Section: Novel Peripherally Restricted Opioidssupporting
confidence: 65%
“…In vitro studies in transfected cells also showed receptor endocytosis induced by END and a correlation between the internalization/signaling potency of opioid ligands and -opioid receptor resensitization (Koch et al, 2005). Other studies of prolonged peripheral opioid receptor activation in the presence of different types of inflammatory stimuli also indicated a lack of tolerance development (Tokuyama et al, 1998;Börzsei et al, 2008;Mangel et al, 2008). These findings imply that the use of peripherally acting opioid agonists for the prolonged treatment of inflammatory pain is not necessarily accompanied by tolerance.…”
Section: Intrinsic Induction Of Opioid Peptide Release From Inflammatmentioning
confidence: 62%
See 2 more Smart Citations
“…However, further large RCTs of the latter drug have been disappointing. [Mangel et al 2008;Szarka et al 2007]. One RCT demonstrated no difference in achievement of the primary end point, average reduction in pain severity 2 hours after treatment, between asimadoline and placebo [Szarka et al 2007], although in a post hoc analysis, there appeared to be a benefit in those with an alternating bowel habit.…”
Section: Drugs Modifying Pain Receptorsmentioning
confidence: 99%